2010
DOI: 10.1248/bpb.33.1165
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Modulates Insulin Sensitivity and Tau Phosphorylation in High Glucose-Induced Hippocampal Neurons

Abstract: Ghrelin is a 28-amino acid brain-gut peptide isolated from rat and human stomach, which is the first endogenous ligand of growth hormone secretagogue receptor 1a (GHSR-1a). 1)Ghrelin exists in the body in two forms: n-octanoyl-ghrelin (ghrelin), which contains an n-octanoyl modification at serine-3 and forms ghrelin's mark structure, and unacylated ghrelin (des-ghrelin). Acylated ghrelin is required for GHSR1a, whereas the unacylated form does not bind to GHSR1a. 2,3) GHSR-1a is widely expressed in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…In fact, ghrelin administration rescued memory deficits and prevented neuronal and synaptic degeneration in the hippocampi of mice injected with Aβ [66]. Furthermore, ghrelin also decreased the levels of hyperphosphorylated Tau via the PI3K/Akt-GSK pathway, in hippocampal neurons [67]. These studies suggest that ghrelin plays a vital role not only in metabolic control, but also in regulating cognitive function and memory capacity.…”
Section: Leptin Amylin and Ghrelinmentioning
confidence: 73%
“…In fact, ghrelin administration rescued memory deficits and prevented neuronal and synaptic degeneration in the hippocampi of mice injected with Aβ [66]. Furthermore, ghrelin also decreased the levels of hyperphosphorylated Tau via the PI3K/Akt-GSK pathway, in hippocampal neurons [67]. These studies suggest that ghrelin plays a vital role not only in metabolic control, but also in regulating cognitive function and memory capacity.…”
Section: Leptin Amylin and Ghrelinmentioning
confidence: 73%
“…AKT is known as protein kinase B (PKB), which is considered an important downstream target of PI3K. It has been reported that high glucose levels decreased activated AKT [41]. PI3K/AKT signaling pathway dysfunction caused increased activity of GSK-3β, which participated in the signal regulating of insulin path and nuclear factor-κ-gene binding (NF-κB) path [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was associated with a shift in the GHS-R1a/GHS-R1b ratio, suggesting an impairment of the autocrine/paracrine mechanisms (Gahete et al 2010). Conversely, ghrelin increases insulin-stimulated neuronal glucose uptake, decreases insulin resistance, and altered tau phosphorylation via the PI3-K/Akt-GSK pathway in hippocampal neuron cultures (Chen et al 2010), suggesting that it may represent a potential treatment. Indeed, in murine models of the disease, treatments with ghrelin or GHS-R1a agonists reduced the levels of amyloid-b peptide and inflammation of the microglia (Dhurandhar et al 2013;Moon et al 2011).…”
Section: Alzheimer's Diseasementioning
confidence: 97%